SRM plume: A candidate as space debris braking system for Just-In-Time Collision avoidance maneuver. (May 2019) - Jarry, A.; Bonnal, C.; Dupont, C.; Missonnier, S.; Lequette, L.; Masson, F.
Abstract: A possible system suited for Just-In Time Collision Avoidance (JCA) is a cloud injected in a sub-orbital trajectory by a sounding rocket that will drag down the passing object because of the local higher density. The sudden deceleration experienced by the debris will after a few revolutions ensure a consistent deviation from its nominal trajectory and therefore will permit a safe reduction of any collision risk with other objects. This article first introduces a feasibility study of such a system, using as baseline an SRM and then enlarges the study to an enhanced system. Highlights: SRM as a candidate for JCA (Just-in-time Collision Avoidance) is analyzed. First computations indicate that a braking target of 1 cm/s is achievable. A further improvement can be achieved with a gas & particle generator (e.g. copper). Braking capabilities up to 125 cm/s can be obtained. Next is the analysis of key parameters (e.g. safety distance, mission feasibility).